2022
DOI: 10.1177/17588359221113266
|View full text |Cite
|
Sign up to set email alerts
|

The presence and size of intrahepatic tumors determine the therapeutic efficacy of nivolumab in advanced hepatocellular carcinoma

Abstract: Purpose: Inter-tumoral heterogeneity at the differential lesion level raises the possibility of distinct organ-specific responses to immune checkpoint inhibitors (ICIs). We aimed to comprehensively examine the clinicopathological factors to predict and assess the efficacy of nivolumab, programmed cell death protein 1 (PD-1) blockade at an individual tumor site-specific level in patients with advanced hepatocellular carcinoma (aHCC). Patients and Methods: We enrolled 261 aHCC patients treated with nivolumab bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…Tumor characteristics are very important for survival in patients with uHCC [ 38 ]. We found that the involved organs and TBS may influence PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor characteristics are very important for survival in patients with uHCC [ 38 ]. We found that the involved organs and TBS may influence PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour characteristics are very important for survival for patients with uHCC [33]. We found that the involved organs and TBS may in uence PFS and OS.…”
Section: Discussionmentioning
confidence: 74%
“…Kim et al [39] found that low LMR was associated with decreased OS in patients with HCC treated with PD-1 inhibitors. Neither Kim et al [39] nor Zhao et al [42] found statistically significant results in investigating the relationship between LMR and PFS.…”
Section: Nlr Plr and Lmrmentioning
confidence: 99%
“…In addition, subgroup analysis found that NLR between 3 and 2.25 was the most appropriate cut‐off value [15]. Kim et al [39] found a trend toward worse OS and PFS with PLR ≥100 in clinical trials of nivolumab in HCC, but this was not statistically significant. Muhammed et al [40] found that PLR may be an independent prognostic factor for OS and PFS after ICI therapy for HCC.…”
Section: Blood Biomarkersmentioning
confidence: 99%